PD-1/PD-L1信号通路在非小细胞肺癌免疫逃逸及其治疗中的研究进展 (Zhongguo Fei Ai Za Zhi, 2014)
Lung cancer is the leading cause of cancer-related mortality worldwide. Despiting the great progress on target agents, majority of people who do not harbor a mutation could not get benefit from them. Immunotherapy, through stimulating the body's immune system to improve the antitumor immunity effect, has been a new therapeutic method for non-small cell lung cancer (NSCLC). Study had been reported that immune checkpoint molecules, including programmed death-1 (PD-1)/PD-ligand (L) 1 axis, are closedly related with cancer generation and development, and play a key role on clinical significance of NSCLC. Activation of PD-1/PD-L1 pathway contributes to tumor immune escape, and block PD-1/PD-L1 pathway can enhance endogenous antimuor immunity. Currently increasing clinical trials suggested that immune checkpoint inhibitors, including anti-PD-1 and anti-PD-L1 monoclonal antibodies turned out to be beneficial and safe in NSCLC. Here, we provide a review on the progress of PD-1/PD-L1 pathway and immune checkpoint inhibitors in NSCLC.